(untitled) (European Journal of Interdisciplinary Research and Development, 2025)
This study explores the nature and functions of implicit expression in both dialogic and monologic discourse. Implicit meaning — communicated without direct articulation — emerges through pragmatic, cognitive, semiotic, and rhetorical strategies that shape interpretation and influence social and aesthetic effects. Drawing on Grice’s theory of conversational implicature, Relevance Theory, and Bakhtin’s distinction between dialogism and monologism, the research analyzes how hidden meanings are constructed differently in interactive versus non-interactive discourse. Dialogic discourse generates implicature through turn-taking, negotiation, and speaker interaction, while monologic discourse encodes implicit content through presupposition, subtext, metaphor, and rhetorical design. The study highlights how these theoretical frameworks explain the mechanisms through which implicit communication operates across discourse types.